SISTEM SIGNAGE RUANG LUAR TERINTEGRASI BANGUNAN STUDI KASUS JAKARTA INTERNATIONAL STADIUM - Pawitra Sari; Retno Fitri Astuti (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2023)
The case study is an international standard stadium with a capacity of 82,000 football spectators creating a diversity of signage in outdoor spaces. Signage is needed by humans to be understood so that it is recorded on cognitive maps. The cognitive map is then translated from the diversity of signage that is cohered into a movement to become an integrated system. This research uses a qualitative method that is analysed descriptively with a case study is the Post Occupancy Evaluation (POE) method. The results show how football spectators understand the various types of signage are colors. The similarity in color indicates integrated zones so that in their cognitive maps there is information to facilitate structured decision making to lead to destination. The same symbol and form of signage refers to international standard rules so that it is easy to guide the spectator. The uniqueness of the signage can be used as a decision point for the next movement. Proper placement in a strategic position in the middle of access roads or circulation paths facilitates legibility and carrying out destination livelihood. Visually on form and function that have similarities or uniqueness can increase awareness and help in orienting oneself and finding destination. In the outdoor space, signage is found that functions as an identification sign, directional sign, and regulatory sign. The success of an integrated signage system can lead spectators from the outdoor space to the inside of the stadium building precisely and quickly.